The shack - Fusco, John; Lanham, Andrew; Cretton, Destin Daniel; Worthington, Sam, 1976-; Spencer, Octavia; Alush, Avraham Aviv; Mitchell, Radha; Braga, Alice; Greene, Graham, 1952-; McGraw, Tim; Young, William P. (Summit Entertainment, 2017)
After suffering a family tragedy, Mack Phillips spirals into a deep depression causing him to question his innermost beliefs. Facing a crisis of faith, he receives a mysterious letter urging him to an abandoned shack deep in the Oregon wilderness.